Manajemen Cairan Pada Pasien Gagal Jantung Dalam Mengurangi Edema dan Kelebihan Cairan - Aris Teguh Hidayat; Fermata Sari; M Yamin; Leny Joice Sianturi (Adi Husada Nursing Journal, 2025)
When evaluating and treating individuals with heart failure, volume overload and fluid congestion are issues. One of the main causes of hospital admission, rehospitalization, and mortality in heart failure is fluid congestion. Reducing congestion and preserving euvolemia is crucial because patients with heart failure who are treated with fluid overload have a higher risk of readmission and/or mortality. Fluid management is one intervention that nurses can use to help patients with heart failure avoid oedema and fluid overload. This systematic study aims to reduce oedema and fluid overload in heart failure patients by identifying fluid management strategies. Data collection methods used online databases: PubMed, Google Scholar, Science Direct, Scopus, ClinicalKey, ClinicalKey Nursing, EBSCOhost, Springer Link, and Sage Journal using the keywords Heart Failure Patient, Fluid Management, Reduce Oedema, and Fluid Overload. Data were analyzed using PRISMA. Based on the review of 5 selected articles, it was found that fluid management was carried out to reduce oedema and fluid overload in patients with heart failure. The primary cause of hospitalization for patients with acute decompensated heart failure (ADHF), which mostly manifests as pulmonary and systemic congestion, is excessive water retention brought on by sodium ion imbalance. For patients with ADHF, relieving congestion is a crucial part of treatment.